Influence of Phytoplankton Advection on the Productivity Along the Atlantic Water Inflow to the Arctic Ocean - Vernet, Maria; Ellingsen, Ingrid H.; Seuthe, Lena; Slagstad, Dag; Cape, Mattias R.; Matrai, Patricia A. (Frontiers in Marine Science, 2019)
Northwards flowing Atlantic waters transport heat, nutrients, and organic carbon in the form of zooplankton into the eastern Greenland Sea and Fram Strait. Less is known of the contribution of phytoplankton advection in this current, the Atlantic Water Inflow (AWI) spanning from the North Atlantic to the Arctic Ocean. The in situ and advected primary production was estimated by using the physical-biological coupled SINMOD model, from northern Norway coast (along the Norwegian Atlantic Current, NAC), the West Spitsbergen Current (WSC) and the entrance to the Arctic Ocean in northern Fram Strait. The simulation results show that changes in phytoplankton biomass at any one location along the AWI are supported primarily by advection. This advection is 5-50 times higher than the biomass photosynthesized in situ, seasonally variable, with minimum contribution in June, at the time of maximum in situ primary production. Advection in the NAC transports phytoplankton biomass from areas of higher production in the south, contributing to the maintenance of phytoplankton productivity further north. In situ productivity further decreases north of Svalbard Archipelago, at the entrance to the Arctic Ocean. Excess in situ annual production in northern WSC is exported to the Arctic Ocean during the growth season (April to September). The balance between in situ and advected primary production defines three main regions along the AWI, presumably modulated by the spatial and temporal variability of copepod grazing. As the sea ice reduces its annual extent and warmer waters enter the Arctic Ocean, ecological characteristics of the ice-free WSC with its AWI signature could extend north and east of Svalbard and into the central Arctic. Advection thus constitutes an important link connecting marine ecosystems of the Arctic and Atlantic Ocean, mainly at the gateways.